Case Report: Metastatic squamous cell carcinoma in the left atrium - Shuai Luo; Xiaoxue Tian; Ting Xu; Jinjing Wang (Frontiers in Cardiovascular Medicine)
BackgroundMetastatic tumours are the most common malignant tumours affecting the heart. Cardiac metastatic tumour progression is rapid, with no specific treatments available, and the prognosis is typically poor. Significant challenges remain in the diagnosis and treatment of cardiac metastases.Case demonstrationA 52-year-old female presented with a history of exertion palpitations lasting over 2 months, worsened by cough and expectoration for 3 days. Colour Doppler echocardiography revealed a hypoechoic mass in the left atrium, which was excised. Postoperative pathology confirmed metastatic squamous cell carcinoma of the left atrium. Six months after surgical removal, the patient remained in good general condition.ConclusionIntracardiac metastasis is extremely rare and presents with non-specific clinical symptoms, often leading to oversight by clinicians. Early diagnosis relies on imaging studies, while definitive diagnosis requires pathological examination. Timely detection is crucial to improving patient prognosis.